The Impact of Labor Unions, Government Regulations and Social Protections on the Efficiency of Labor Market - Yau, Aminu (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Labor market is such a crucial area in every economy, that necessitates certain regulations and protections in the overall activity of the market, through government intervention, labor unions and social protections institutions, ultimately to protect the interest of the employees, employers and other relevant stakeholders in the market, with the soul aim of increasing the efficiency of the labor market in general. This research study tries to assess the impact of these regulations and labor institutions on the efficiency of the labor market. The study collected a across-sectional data from 80 developed and less developed countries, and applied an ordinary least squared (OLS) regression model to assess the impact of government regulation, labor unions and social protection on the efficiency of labor market across the developed and less developed countries, in an attempt to figure out whether these institutions and regulations achieved the aims and objectives, which is to enhance the overall efficiency of the labor market based on labor market institutions efficiency theory. The result shows that despite the fact that government regulation, labor unions and social protection have some significant positive impact on the efficiency of labor market, the variables also have negative impact on the labor market efficiency in some other ways, which create some forms of distortion in the market. Moreover, the result shows that these impacts differ across developed and less developed countries significantly. Keywords: Labor market, Government regulations (Minimum wage rate), Labor union density, Labor market efficiency, Social protections (social institutions)

ÖZ: İşgücü piyasası her ekonomide önemli bir sektördür, bu yönetimin emek sendikaları ve sosyal müdahale korumaları kurumlar aracılığıyla pazarın genel aktivitesinde belli düzenlemeler ve korumalar gerektirmektedir. Genel olarak Bu araştırma çalışmasında İşçi piyasasının etkinliğinin artırılması, piyasada işçi, işveren ve diğer ilgili paydaşların çıkarını korumak ve verimliliği arttırmak amacıyla bu yönetmelik İşçi etkisini değerlendirmek için çalışır İşgücü piyasası. Gelişmiş ve Az Gelişmiş ülkelerin verileri toplamış ve yönetimin duzenlı etkisini değerlendirmek için sıradan bir OES regresyon modeli uygulanmıştır. Bu instinutions ve yönetmelikler Çalışma dayalı İşçi piyasasının genel verimliliği artırmak için, hangi amaç ve hedefleri elde olmadığını anlamaya bir girişim Laior armions ve geliştirilen ve daha az sosyal geliştirilen ülkede İşgücü piyasası, verimliliği koruma piyasa Kurumları verimlilik teorisi sonucu yönetimin daha repa ation, İşçi sendikaları ve sosyal koruma İşgücü piyasası verimliliği üzerinde bazı önemli pozitif bir etkiye sahip olmasına rağmen, değişkenler de diğer bazı yollarla İşgücü piyasası verimliliği üzerinde olumsuz bir etkiye sahip olduğunu göstermektedir. Ayrıca, sonuç bu etkilerin önemli ölçüde gelişmiş ve az gelişmiş ülkeler arasında hangi pazarda bozulma formlarının oluşum farlılıklarını gösterir
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2016. Supervisor: Assoc. Prof. Dr. Sevin Uğural.
Keywords: Economics; Labor Market - Labor Economics; Labor Unions; Labor market; Government regulations (Minimum wage rate); Labor union density; Labor market efficiency; Social protections(social institutions)